Bayesian trial of adalimumab versus secukinumab for children with juvenile idiopathic arthritis associated uveitis or chronic anterior uveitis - Athimalaipet V Ramanan; Andrew D Dick; Thomas Jaki; Gianmarco Caruso; David S Robertson; Ashley P Jones; Ben Hardwick; Sian Drake; Balini Balasubramaniam; Coziana Ciurtin; Ivan Foeldvari; Elke O Kreps; et al. (Pediatric Rheumatology Online Journal)
Abstract Background Juvenile idiopathic arthritis (JIA)-associated uveitis and chronic anterior uveitis in children may result in permanent sight loss. Currently, the only licensed and approved treatment for JIA-uveitis is adalimumab. However, even in patients where adalimumab may be initially effective, therapeutic response may subside for example, due to neutralising drug antibodies. Further treatment options are necessary to prevent sight loss in children with uveitis. Interleukin 17 is elevated in uveitis. Inhibition of interleukin 17 ameliorates inflammation in mouse models of uveitis. Secukinumab, an antibody which neutralizes interleukin 17 A, has been shown to be partially effective in adult uveitis. The objective of the Bayesian consensus meeting was to quantify prior expert opinion about the potential utility of secukinumab in treatment of uveitis in JIA. Methods Nine international experts in paediatric rheumatology, paediatric ophthalmology and/or paediatric uveitis took part in a structured Bayesian prior elicitation meeting. Results The final consensus was that adalimumab is expected to yield a higher response rate than secukinumab (mean 0.67 vs. 0.55). The uncertainty in the response rate on secukinumab is somewhat larger than for adalimumab. The equivalent sample size for the prior distribution of adalimumab is 15.7 and 13.1 for secukinumab. The decisions based on the combined evidence would still be driven by the trial data, yet substantial enhancement of the power of the study can be expected by adding information from the equivalent of almost 30 patients. Conclusions The Bayesian analysis adds substantial enhancement of the power of the study and supports a head-to-head trial of adalimumab and secukinumab for JIA-associated uveitis and chronic anterior uveitis. Trial registration ISRCTN 12,427,150 Registration date 14/02/2023. EudraCT 2022-003068-26 Registration date 07/09/2022.